2005
DOI: 10.1002/bies.20208
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution theory of the genetic code at age thirty

Abstract: The coevolution theory of the genetic code, which postulates that prebiotic synthesis was an inadequate source of all twenty protein amino acids, and therefore some of them had to be derived from the coevolving pathways of amino acid biosynthesis, has been assessed in the light of the discoveries of the past three decades. Its four fundamental tenets regarding the essentiality of amino acid biosynthesis, role of pretran synthesis, biosynthetic imprint on codon allocations and mutability of the encoded amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
182
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(192 citation statements)
references
References 102 publications
9
182
0
1
Order By: Relevance
“…Innovations in the genetic code might also move through populations by horizontal gene transfer (32). It has been suggested that, during early cellular evolution, new genetically encoded amino acids joined more ancient ones as novel biosynthetic pathways arose that used older amino acids and their precursors (33)(34)(35)(36). Newer amino acids joined the growing genetic code by charging of their own tRNA species that allowed interpretation of a codon as the new recruit to the genetic code, even while the older codon function was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Innovations in the genetic code might also move through populations by horizontal gene transfer (32). It has been suggested that, during early cellular evolution, new genetically encoded amino acids joined more ancient ones as novel biosynthetic pathways arose that used older amino acids and their precursors (33)(34)(35)(36). Newer amino acids joined the growing genetic code by charging of their own tRNA species that allowed interpretation of a codon as the new recruit to the genetic code, even while the older codon function was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Relationships between biosynthetic pathways and codon assignments find statistical support in the organization of the present code where biosynthetically related amino acids share codon boxes (Wong 2005). …”
Section: Introductionmentioning
confidence: 79%
“…Prebiotic chemistry on early Earth did not supply all 20 current protein amino acids (see part 5.2) and most likely some of them had a biosynthetic origin. The expanding amino acid repertoire might have therefore coevolved with the code, namely new metabolic products could usurp codons previously used by their metabolic precursors (for a recent review, see Wong, 2005). 5.6.1.7.…”
Section: An Expanding Codementioning
confidence: 99%